2020
DOI: 10.1177/1044207320934048
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Impact of Design Standards on the Rigor of a Subset of Single-Case Research

Abstract: The implementation of research-based practices by teachers in public school classrooms is required under federal law as expressed in the Individuals With Disabilities Education Improvement Act of 2004. To aid teachers in identifying such practices, researchers conduct systematic reviews of the educational literature. Although recent attention has been given to changes in the quality of these reviews, there has been minimal discussion about changes in the quality of the studies that comprise them. Specifically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Many researchers view the RAD as strictly a comparative design, in which they used RAD to compare the effects of two or more interventions (Kennedy, 2005;Ledford & Gast, 2018;Shepley et al, 2020). However, researchers can use a RAD for either inductive/dynamic comparisons or to address deductive/static research questions (Johnson & Cook, 2019).…”
Section: Design Appropriately Matches the Behavior Of Interest And Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers view the RAD as strictly a comparative design, in which they used RAD to compare the effects of two or more interventions (Kennedy, 2005;Ledford & Gast, 2018;Shepley et al, 2020). However, researchers can use a RAD for either inductive/dynamic comparisons or to address deductive/static research questions (Johnson & Cook, 2019).…”
Section: Design Appropriately Matches the Behavior Of Interest And Research Questionsmentioning
confidence: 99%
“…At the same time, intervention researchers often rely on group designs, even when such designs are underpowered, or the novel intervention is still in the development phase. The second reason could be that a basic RAD study cannot sufficiently control for threats to internal validity like history, maturation, and testing effects, as many critiques have suggested (Kennedy, 2005;Ledford & Gast, 2018;Shepley et al, 2020). In Figure 1A, the basic RAD lacks a baseline and an ongoing control condition that would strengthen the study's internal validity.…”
mentioning
confidence: 99%
“…Under the above guidelines, the author based on previous studies identifying broad common categories of rigor (Gibbert et al , 2008; Gibbert and Ruigrok, 2010; Goffin et al , 2019; Hoorani et al , 2019; Perks and Roberts, 2013; Runfola et al , 2017; Elsahn et al , 2020) or considering rigor and transparency (Farquhar et al , 2020; Shepley et al , 2020), along with other methods (Lincoln and Guba, 1985; Anderson, 2012; Foxall, 1988; Goffin et al , 2019; Gibbert and Ruigrok, 2010; Eisenhardt and Graebner, 2007). Some representative studies are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Rigor is an important part of scientific research, it ensures the validity of the research results and provides a solid foundation for further (Conn and Ritala, 2019; Ketokivi and Choi, 2014; Molina-Azorin and Fetters, 2020). Therefore, transparency, reliability and validity, are essential in the evaluation index system of case studies (Aguinis and Solarino, 2019; O’Kane et al , 2019; Shepley et al , 2020). Despite the acknowledged importance, there is a lack of consensus on the criteria that lead to rigorous qualitative research (Morse et al , 2016; Hoorani et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The increased attention to rigor of SCD studies is encouraging-guidance regarding what should be accepted as adequate evidence may ultimately lead to the conduct and publication of studies whose outcomes are believably attributable to the independent variables manipulated by researchers (although there is some evidence that standards have not yet resulted in subsequent research improvements; Shepley et al, 2021). One conceivable downside of the attention to rigor is the potential to disregard important pilot work, including bodies of work that consistently show the same effects but for which some aspects of rigor are difficult to accomplish.…”
mentioning
confidence: 99%